Perbandingan Tool Forensik pada Mozilla Firefox Private Mode Menggunakan Metode NIST - Sarjimin Sarjimin; Herman Herman; Anton Yudhana (Jurnal Algoritma, 2021)
Linux Operating System which is distributed as open source makes it an operating system that can be distributed massively by many companies. Linux-based PCs / Notebooks and smart devices are increasingly in demand by users because the distribution process is free of charge. Providing internet browsing services to users privately and leaving no digital footprint is one of the efforts made by the web browser as an effort to innovate the web browser to get as many service users as possible. The private mode web browser forensic investigation method is necessary to become a reference in conducting forensic cases / incidents of crime involving private browsing services. There are many tools that can be used to perform live forensics and data analysis. This research success to reveal that the private browsing service provided by Mozilla Firefox is not completely private. Digital artifacts can still be found in RAM and analyzed using a variety of forensic tools, Autopsy tools success to acquired 83% of web browser log. The results of these investigative artifacts can serve as a starting point for investigators in law enforcement to look for other suspects and explore a case that involves many parties.